A caminhabilidade como instrumento de humanização de travessias urbanas rodoviárias - Raquel Corrêa Lacerda Dutra (2020)
Urban road crossings - urban areas segmented by highways - are complex regions caused by the conflict between transit traffic and local traffic. In this context, it is possible to observe that pedestrians appear as the most vulnerable elements in a mobility microsystem, bearing in mind that, traditionally, the ultimate goal to be achieved is optimal traffic flow. Therefore, studying pedestrian traffic in urban stretches of Brazilian highways becomes a challenge in view of the research incentive aimed at other means of transportation. Over the last decades, despite some actions have been taken regarding improvements of infrastructure aimed at pedestrians in different types of urban road crossings, it is necessary to increase actions towards transforming urban road areas into spaces that are more friendly and safe for pedestrian traffic. For this purpose, methodologies that are able to understand the environment of pedestrians, which are areas scarcely researched up to now, are extremely relevant. Applying an index that can be used as an assessment tool of the environment in which pedestrians are inserted becomes of utmost importance in an effort to better understand the quality of a certain spatiality. In this context, the goal of this dissertation is to develop a walkability index that allows for the assessment of the quality of the environment intended for pedestrian traffic in urbanized areas surrounding highways. From this point of view, two stretches of the state highway MG-10, located in the municipality of Lagoa Santa, Minas Gerais were selected for this research. The index was conceived in 5 stages. The first stage consisted of identifying, in national and international literature, indicatorsthat help measuring walkability conditions; after that, these indicators were assessed as it concerns their applicability for urban stretches segmented by highways. The second stage consisted of adapting the walkability index produced by Carvalho (2018), whose work is developed/continued in this dissertation, as a basis for the preparation of an index to be applied to urban road crossings. The third stage consisted of the preparation and application of a questionnaire survey among highway professionals in an attempt to identify the significance level of the indicators used in Carvalho’s (2018) research. The fourth stage was concerned with the development of a walkability index for urban road crossings and, finally, the fifth stage consisted of applying the proposed walkability index in two different spatialities of the same urban road crossing. The proposed methodology has been found to be accessible and easy to understand, taking into account, whenever possible, a quantitative analysis of the elements, making the index application a quickly executable method. The index created was used for the assessment of two spatialities, one consisting of 8 segments and the other consisting of 6 segments of the MG-10 highway. The use of the index proved to be efficient in the assessment of walkability in urban crossings, showing that it can be used in other spatialities or road stretches with similar features. Also, it was noted that the index can be an important tool on the definition of new projects as well as for correcting existing situations. Finally, the study presented here points out the need for a deeper investigation of issues related to improving the walkability of pedestrians across urban road crossing.